INTERPERSONAL COMMUNICATION OF HUSBANDS FOR BUILDING HARMONY IN FAMILY - Muhammad Bisri Mustofa; Siti Wuryan (INTERCODE, 2023)
This study aims to analyze the concept of husband's interpersonal communication inbuilding harmony within Muslim couples, considering the perspective of Islamic law.The method used in this research is a literature review, which involves analyzing variousrelevant literature sources on this topic. The results of this literature review analysis revealthat husband's interpersonal communication plays a crucial role in building harmonywithin Muslim couples. In the context of family, good and affectionate communicationbetween husband and wife is considered a manifestation of religious teachings thatencourage cooperation, mutual understanding, and support in marriage. To carry outeffective interpersonal communication, husbands need to have the ability to listen, respecttheir wife's opinions, and provide emotional support. This research contributes tounderstanding the importance of interpersonal communication in the context of familybased on Islamic teachings, as well as providing insights into how husbands can buildharmony in marital relationships.Keyword: Interpersonal Communication, Harmony, Family